CHARACTER EDUCATIONIN KHALED HOSSEINI’S NOVEL AND THE MOUNTAINS ECHOED - Anita, Anita; Emzir, Emzir (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The aim of this research is to obtain a deep understanding of character education in And The Mountains Echoed Novel written by Khalid Hosseini. This research used qualitative approach, content analysis method, through structuralism and semiotics study. Structurally, character education in this novel found in the theme, the plot, the characters and characterization, and the setting. Semiotically, the researcher found semiotics signs in And The Mountains Echoed novel relating to the character education, namely, index, symbol, and icon. The data were collected through a carefull reading of the novel, identification, and classification. The values taken are the combination between character education value from Pusat Kurikulum Balitbang Diknas and Lickona’s. However not all values are captured, among the 28 values, only thirteen caught from the novel. The values are hard working, religious, responsible, love, integrity, social care, never give up, thanks be to Allah, appreciating achievement, wisdom, creative, curiousity, and friendly/communicative. From the structure of the novel, the character education implemented explicitly and implicitly in the theme, the character and characterization, the setting, and the plot. While from the semiotics, the character education mostly found in the form of index, followed by symbol,and then icon.